Evaluation of the occurrence, degradation, and ecotoxicological significance of pharmaceuticals as emerging contaminants of concern in wastewaters and surface waters of the urban area in Costa Rica - Ledezma-Espinoza, Aura (2023)
Tesis (Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión y Cultura Ambiental) Instituto Tecnológico de Costa Rica. Universidad Estatal a Distancia. Universidad Nacional, Doctorado en Ciencias Naturales para el Desarrollo, 2023.